Framework-based teaching of MFRS: Challenges to accounting lecturers / Zuhariah Husin …[et al.] - Husin, Zuhariah; Mat Bahari, Anis Barieyah; Mohd Din, Norlaila; Abd Wahab, Roslan (2013)
The full adoption of International Financial Reporting Standards which is based on the conceptual framework through the issuance of Malaysian Financial Reporting Standards (MFRS) has led to the framework-based teaching of MFRS (FBT MFRS) with the aim of producing accounting graduates that is equipped with interpretive and judgmental skills of the standards. The framework-based teaching of MFRS is focusing on the principle of financial reporting standards as opposed to the rule-based teaching method currently practiced. The new teaching approach comes with some challenges namely training on the new approach, familiarization period, preparation of teaching materials and students' assessment and availability of experts on the new approach. Survey questionnaires were distributed to all accounting lecturers of Universiti Teknologi MARA Pahang with the aim to identify the perceived challenges in implementing the framework-based teaching of MFRS. It was found that the main challenges were training on the new approach and familiarization period whereas the remainders are of secondary concern. A number of recommendations to overcome the challenges of implementing framework-based teaching of MFRS are approved training opportunities to the lecturers involved with FBT MFRS by the relevant faculty or campus authorities, ample time given to accounting lecturers to familiarize themselves with the approach before its implementation and appointment of expert on FBT MFRS in the before or in the early stages of implementation.